The Influence of Product Quality and Service Quality on Consumer Satisfaction at a Restaurant in Jakarta - Puput Pratiwi; Retno Resawati (Jurnal Computech & Bisnis (e-journal), 2024)
The objective of this study is to gather data, facts, and information about the quality of the product and service at a restaurant in Jakarta, analyze it, and draw conclusions in order to determine the impact of product and service quality on consumer satisfaction at the restaurant. The research was meticulously conducted over two months, commencing in October 2018, with the target population being the consumers of Nasi Kebuli Kebun Nanas Restaurant in Jakarta. A total of 94 individuals were involved in this comprehensive study, which employs descriptive research methodology. This study employs descriptive research methodologies. Descriptive research examines current facts pertaining to a specific problem obtained from a representative sample to examine hypotheses or address inquiries pertaining to the present condition of the subject being investigated. The variables Product Quality and Service Quality, which are crucial in understanding consumer satisfaction, are considered independent variables, denoted as X1 and X2, respectively. User Satisfaction is the dependent variable, denoted as Y. The calculation of the coefficient of determination R2 (R squared) provides a measure, expressed as a percentage, that describes the extent to which the independent variables, namely product quality (X1) and service quality (X2), contribute to the variations in consumer satisfaction at the Nasi Kebuli Kebun Nanas Restaurant in Jakarta. The variable (Y) accounts for 58.6% of the total, while the remaining 41.4% is attributed to other factors that are analyzed and also impact employee performance.